(untitled) (Fiep Bulletin - online, 2014)
The present study is centered in the discipline area of sportive management in the participation sports, where we objectify the conception of a Sequential Course in Communitarian Sportive Management of Specific Formation, distance-based and destined to leaders of Communitarian Sportive Leagues (71) and Associations of Quarters (211) of the city of Manaus, in number of 4 Entities in a total of 1128 participants, which must have finished high school and not yet have graduate from college. The course intends to offer a formation of specific character, humanist and will make possible a professional intervention of critical form, based on the ethical behavior, assuring still the theory-practice are indissociable by means of the practical use as a curricular component. It will be developed in 5 periods and with a load of 1640 hours/classes. In addition to their curricular structures, the participants will have to fulfill activities as component curricular and at the end to deliver a conclusive paper.